Rearing and Injection of Manduca sexta Larvae to Assess Bacterial Virulence - Hussa, Elizabeth (MyJove Corporation, 2012)
Manduca sexta, commonly known as the tobacco hornworm, is considered a significant agricultural pest, feeding on solanaceous plants including tobacco and tomato. The susceptibility of M. sexta larvae to a variety of entomopathogenic bacterial species(1-5), as well as the wealth of information available regarding the insect's immune system(6-8), and the pending genome sequence(9) make it a good model organism for use in studying host-microbe interactions during pathogenesis. In addition, M. sexta larvae are relatively large and easy to manipulate and maintain in the laboratory relative to other susceptible insect species. Their large size also facilitates efficient tissue/hemolymph extraction for analysis of the host response to infection. The method presented here describes the direct injection of bacteria into the hemocoel (blood cavity) of M. sexta larvae. This approach can be used to analyze and compare the virulence characteristics of various bacterial species, strains, or mutants by simply monitoring the time to insect death after injection. This method was developed to study the pathogenicity of Xenorhabdus and Photorhabdus species, which typically associate with nematode vectors as a means to gain entry into the insect. Entomopathogenic nematodes typically infect larvae via natural digestive or respiratory openings, and release their symbiotic bacterial contents into the insect hemolymph (blood) shortly thereafter(10). The injection method described here bypasses the need for a nematode vector, thus uncoupling the effects of bacteria and nematode on the insect. This method allows for accurate enumeration of infectious material (cells or protein) within the inoculum, which is not possible using other existing methods for analyzing entomopathogenesis, including nicking(11) and oral toxicity assays(12). Also, oral toxicity assays address the virulence of secreted toxins introduced into the digestive system of larvae, whereas the direct injection method addresses the virulence of whole-cell inocula. The utility of the direct injection method as described here is to analyze bacterial pathogenesis by monitoring insect mortality. However, this method can easily be expanded for use in studying the effects of infection on the M. sexta immune system. The insect responds to infection via both humoral and cellular responses. The humoral response includes recognition of bacterial-associated patterns and subsequent production of various antimicrobial peptides(7); the expression of genes encoding these peptides can be monitored subsequent to direct infection via RNA extraction and quantitative PCR(13). The cellular response to infection involves nodulation, encapsulation, and phagocytosis of infectious agents by hemocytes(6). To analyze these responses, injected insects can be dissected and visualized by microscopy(13, 14).